SPORTS BUSINESS: THE ROLE OF BUSINESS INTELLIGENCE IN BUSINESS SUCCESS IN SPORTS FIELD RENTAL - Achmad Fauzi; Ahmad Muchlisin Natas Pasaribu; Muzakki Sudirman; Ratilla Amanda Edwar; Teti Aliyanti; Lola Kambuno; Reifa Galih Ramadhanti; Putri Ayu Shayekti Melani; Jhonni Sinaga (Draf Solusi Indonesia, 2023)
In business there is the science of collecting accurate data and information that can be obtained from various sources, this knowledge is called Business Intelligence. This knowledge can help to provide appropriate options for business needs. The method used in writing this journal is a qualitative method, namely a method that collects previous research data as reference material for this journal research, how much influence one variable has on another. Business Intelligent is used to identify customer satisfaction in renting sports fields by collecting data from various sources using technology. Business Intelligent can strategically identify field locations leased to customers. This journal has literature results in the form of: 1) Customer satisfaction with sports field rentals; 2) The influence of Business Intelligent on sports field rental costs that are affordable for strategic locations.